Scratch-resistant protective film for automobile and preparation method of scratch-resistant protective film
Through the coating design of modified nano-alumina and modified polyurethane acrylate, combined with the synergistic effect of photoinitiators and antioxidants, the problems of low hardness, poor wear resistance and insufficient weather resistance of traditional automobile protective films are solved, and high-performance automobile surface protection is achieved.
Patent Information
- Application Number
- CN202510836525.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-21
- Publication Date
- 2025-09-26
AI Technical Summary
Traditional car protective films have low hardness, poor wear resistance, weak adhesion and insufficient weather resistance, and cannot effectively protect the car surface. They are also prone to aging and falling off after long-term use.
The coating design combines modified nano-alumina with modified polyurethane acrylate. Through the esterification modification of the nano-alumina surface and the cross-linking reaction of polyurethane acrylate, a coating with high hardness, wear resistance and weather resistance is formed. With the synergistic effect of photoinitiators and antioxidants, the curing process of the coating is optimized to improve performance.
It achieves high hardness (pencil hardness ≥ 2H), strong adhesion (100-grid test shedding rate ≤ 5%) and long-term weather resistance (yellowing rate after UV aging ≤ 10%). The coating has both wear resistance (friction times ≥ 5000 times) and impact resistance, adapts to complex automotive working conditions, and meets green manufacturing standards.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of automobile surface protection materials, and in particular to an automobile anti-scratch protective film and a preparation method thereof. Background Art
[0002] With the continued growth in car ownership, consumers are increasingly demanding higher levels of protective performance for their vehicles' surfaces. Traditional automotive protective films (such as PVC films and standard TPU films) often suffer from insufficient hardness, weak scratch resistance, and poor adhesion to car paint. They are easily scratched or even peeled off by daily friction, stone impacts, or key nicks. This not only affects the appearance of the car but also fails to effectively protect the original paint finish. Furthermore, traditional coatings often rely on simple physical blending processes to add fillers. This results in uneven dispersion of nanoparticles, which easily agglomerate, leading to weak interfacial bonding and difficulty in simultaneously improving the coating's hardness and flexibility, limiting their practical application.
[0003] While existing technologies have attempted to optimize filler dispersion through surface modification (e.g., using silane coupling agents to modify nanoparticles) or to improve performance through adjustments to the resin system (e.g., using a single polyurethane acrylate), significant limitations remain. Silane modification requires strict control of reaction conditions (e.g., temperature and pH), otherwise hydrolysis and inactivation can occur, leading to filler reagglomeration. Furthermore, single resin systems struggle to balance hardness and flexibility. While hard resins increase hardness, they also increase brittleness, while soft resins lack the required hardness to meet the demands of complex automotive applications. Furthermore, traditional coatings lack weather resistance (yellowing and decreased hardness after UV aging) and aging resistance (e.g., the limited use of antioxidants). Long-term outdoor use can lead to coating degradation and shedding, making them ineffective for long-term protection.
[0004] Therefore, there is an urgent need to develop an automotive surface protection material with excellent comprehensive performance, which can not only significantly improve the hardness and wear resistance through high-efficiency filler modification, but also achieve a balance between flexibility and adhesion through resin system optimization, while taking into account weather resistance and aging resistance, so as to solve the problems of existing protective films such as easy scratching, easy falling off, and poor durability, and provide long-term and reliable protection for automotive surfaces. Summary of the Invention
[0005] The purpose of the present invention is to provide an automobile anti-scratch protective film and a preparation method thereof, which solves the problems of traditional automobile protective materials such as low hardness, poor wear resistance, weak adhesion and insufficient weather resistance.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions: An automobile surface protective material, wherein the raw materials thereof include, by mass percentage: Modified nano-alumina: 5-15%; Modified polyurethane acrylate: 20-35%; Polyurethane acrylate: 25-40%; Photoinitiator: 3-8%; Leveling agent: 0.5-2%; Antioxidant: 0.5-1.5%; Solvent: balance; The preparation steps of the modified nano-alumina include: adding nano-α-Al2O3 to anhydrous ethanol and ultrasonically dispersing until uniform dispersion; adding stearic acid to the dispersion, heating to 80-90°C and reflux reaction, continuously stirring during the reaction to promote the esterification reaction between hydroxyl groups and stearic acid; filtering while hot after the reaction is completed, washing the filter cake with anhydrous ethanol three times, and finally drying in a vacuum.
[0007] According to a preferred embodiment of the present invention, the polyurethane acrylate is purchased from Wanhua Chemical Group Co., Ltd.
[0008] According to a preferred embodiment of the present invention, the nano α-Al2O3 is purchased from Evonik Specialty Chemicals (Shanghai) Co., Ltd.
[0009] According to a preferred embodiment of the present invention, the anhydrous ethanol is purchased from Sinopharm Chemical Reagent Co., Ltd.
[0010] According to a preferred embodiment of the present invention, the stearic acid is purchased from Sime Darby Petroleum Berhad of Malaysia.
[0011] According to a preferred embodiment of the present invention, the preparation steps of the modified nano-alumina include: the particle size of the nano-α-Al2O3 is 40-100nm, the ultrasonic dispersion time is 50-70min; the particle size of the dispersion liquid is ≤120nm; the reflux reaction time is 4-6h; the vacuum drying temperature is 80-100℃ and the drying time is 20-24h.
[0012] In the preparation process of the modified nano-alumina of the present invention, a large number of hydroxyl groups (-OH) exist on the surface of the nano-α-Al2O3. After ultrasonic dispersion in anhydrous ethanol (50-70 minutes), the particle size of the dispersion is reduced to ≤120nm, forming a uniform nano-suspension system. After adding stearic acid, the temperature is raised to 80-90°C for reflux reaction (4-6 hours), and the carboxyl groups (-COOH) in the stearic acid molecules react with the hydroxyl groups on the surface of the nano-alumina to form a stable long-chain fatty acid ester layer (stearic acid ester). The ester layer is coated on the surface of the nano-alumina through physical adsorption and chemical bonding, reducing its surface energy and inhibiting agglomeration, thereby improving the stability of the dispersion. After the reaction, the mixture is filtered while hot and the filter cake is washed with anhydrous ethanol three times to remove unreacted stearic acid and solvent. Finally, the mixture is vacuum dried at 80-100°C (20-24 hours) to obtain a modified nano-alumina with ester groups on the surface. The surface ester groups can form hydrogen bonds or covalent bonds with hydroxyl groups or amino groups in a subsequent polyurethane acrylate resin to enhance interfacial bonding.
[0013] According to a preferred embodiment of the present invention, the preparation steps of the modified polyurethane acrylate include: adding polycaprolactone diol and hexamethylene diisocyanate into a three-necked flask equipped with a stirrer and a thermometer, introducing nitrogen protection, heating to 75-85°C for reaction to obtain an isocyanate-terminated polyurethane prepolymer; adding hydroxyethyl methacrylate and dibutyltin dilaurate to the prepolymer, heating to 85-95°C for reaction to obtain a hydroxyl-terminated polyurethane; and then adding hydroxyethyl acrylate and 1-hydroxycyclohexyl phenyl ketone to the system to continue the reaction.
[0014] According to a preferred embodiment of the present invention, the polycaprolactone diol is purchased from Wanhua Chemical Group Co., Ltd.
[0015] According to a preferred embodiment of the present invention, the hexamethylene diisocyanate is purchased from Covestro Polymers (China) Co., Ltd.
[0016] According to a preferred embodiment of the present invention, the hydroxyethyl methacrylate is purchased from Wanhua Chemical Group Co., Ltd.
[0017] According to a preferred embodiment of the present invention, the dibutyltin dilaurate is purchased from Akzo Nobel Protective Coatings (Suzhou) Co., Ltd.
[0018] According to a preferred embodiment of the present invention, the hydroxyethyl acrylate is purchased from BASF (China) Co., Ltd.
[0019] According to a preferred embodiment of the present invention, the 1-hydroxycyclohexyl phenyl ketone was purchased from BASF (China) Co., Ltd.
[0020] According to a preferred embodiment of the present invention, the reaction time when the temperature is raised to 75-85°C is 3-4 hours; the reaction time when the temperature is raised to 85-95°C is 2-3 hours; and the reaction time is continued for 1.5-2 hours.
[0021] In the preparation process of the modified polyurethane acrylate of the present invention, the terminal hydroxyl group (-OH) of polycaprolactone diol (molecular weight 1500-2000) and the isocyanate group (-NCO) of hexamethylene diisocyanate (HDI) undergo a stepwise addition reaction under nitrogen protection (75-85°C, 3-4h) to generate an isocyanate-terminated polyurethane prepolymer (-NHCOO- repeating unit, with an unreacted -NCO group remaining at the end); hydroxyethyl methacrylate (HEMA, containing -OH) and dibutyltin dilaurate ( Catalyst), heat to 85-95℃ (2-3h), the -NCO at the end of the prepolymer continues to react with the -OH of HEMA to generate hydroxyl-terminated polyurethane (-NHCOO- repeating unit, with -OH at the end); then add hydroxyethyl acrylate (containing double bond) and 1-hydroxycyclohexyl phenyl ketone (photoinitiator) to the system, and continue the reaction (1.5-2h), so that the double bond of hydroxyethyl acrylate reacts with the hydroxyl group at the end of the polyurethane chain to finally form hydroxyl-terminated polyurethane containing polymerizable double bonds, which provides active sites for subsequent photocuring.
[0022] According to a preferred embodiment of the present invention, the photoinitiator is selected from at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the leveling agent is selected from at least one of BYK chemical silicone leveling agents, polyether modified polydimethylsiloxane and acrylate leveling agents.
[0023] According to a preferred embodiment of the present invention, the 2-hydroxy-2-methyl-1-phenyl-1-propanone is purchased from BASF (China) Co., Ltd.
[0024] According to a preferred embodiment of the present invention, the 1-hydroxycyclohexyl phenyl ketone is purchased from BASF (China) Co., Ltd.
[0025] According to a preferred embodiment of the present invention, the 2,4,6-trimethylbenzoyl-diphenylphosphine oxide is purchased from Akzo Nobel Protective Coatings (Suzhou) Co., Ltd.
[0026] According to a preferred embodiment of the present invention, the BYK silicone leveling agent is purchased from BYK Chemical (China) Co., Ltd.
[0027] According to a preferred embodiment of the present invention, the polyether-modified polydimethylsiloxane is purchased from Evonik Specialty Chemicals (Shanghai) Co., Ltd.
[0028] According to a preferred embodiment of the present invention, the acrylic leveling agent is purchased from Yu Deqian Chemical (Shanghai) Co., Ltd.
[0029] According to a preferred embodiment of the present invention, the antioxidant is selected from at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylphenyl) phosphite and didodecyl thiodipropionate; and the solvent is ethyl acetate.
[0030] According to a preferred embodiment of the present invention, the pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] was purchased from BASF (China) Co., Ltd.
[0031] According to a preferred embodiment of the present invention, the tris(2,4-di-tert-butylphenyl) phosphite is purchased from BASF (China) Co., Ltd.
[0032] According to a preferred embodiment of the present invention, the didodecyl thiodipropionate is purchased from Kingfa Science & Technology Co., Ltd.
[0033] According to a preferred embodiment of the present invention, the ethyl acetate is purchased from Sinopharm Chemical Reagent Co., Ltd.
[0034] The present invention also provides a method for preparing the automobile surface protective material, comprising the following steps: S1. Add modified nano-alumina to a solvent and disperse it uniformly by ultrasonication; add modified polyurethane acrylate, basic polyurethane acrylate, photoinitiator, leveling agent and antioxidant to the dispersion in sequence, and stir and mix uniformly to obtain a functional coating slurry; S2. The functional coating slurry is evenly applied to the surface of the PET substrate by a doctor blade, and the coated substrate is placed in an oven for pre-drying; S3. Irradiate with a UV curing machine to complete the coating curing.
[0035] According to a preferred embodiment of the present invention, in step S1, the ultrasonic dispersion time is 30-40 min; the stirring speed is 300-400 rpm, and the stirring time is 25-30 min.
[0036] In the mixing process of the functional coating slurry of the present invention, modified nano-alumina (5-15%) is added to a solvent (ethyl acetate, the balance) and ultrasonically dispersed (30-40 minutes) until uniform, and then modified polyurethane acrylate (20-35%), basic polyurethane acrylate (25-40%), photoinitiator (3-8%), leveling agent (0.5-2%) and antioxidant (0.5-1.5%) are added in sequence, and stirred at 300-400 rpm (25-30 minutes) to form a Uniform slurry; wherein, the ester group on the surface of modified nano-alumina is bonded to the hydroxyl group of modified polyurethane acrylate through hydrogen bonds or covalent bonds, the leveling agent (such as BYK silicone) reduces the surface tension of the coating to avoid defects such as orange peel and shrinkage, the antioxidant (such as pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) captures free radicals to inhibit oxidative degradation, and the photoinitiator (such as 1-hydroxycyclohexyl phenyl ketone) decomposes under ultraviolet light to produce free radicals, providing active centers for subsequent curing.
[0037] According to a preferred embodiment of the present invention, in step S2, the thickness of the PET substrate is 40-70 μm, the coating thickness is 20-40 μm, the pre-drying temperature is 80-100° C., and the pre-drying time is 10-15 minutes.
[0038] During the coating and pre-drying process of the present invention, the functional coating slurry is evenly coated on the surface of a PET substrate (thickness 40-70 μm) by a doctor blade to form a wet film 20-40 μm thick. Subsequently, the coating is pre-dried at 80-100°C (10-15 minutes) to evaporate and remove the solvent (ethyl acetate). The coating is initially cured to form a semi-dry film. Controlling the pre-drying temperature and time can avoid solvent residue (≤2%) and microcracks caused by stress concentration in the coating.
[0039] According to a preferred embodiment of the present invention, in step S3, the wavelength of the ultraviolet light is 365 nm, the light intensity is 1000-1500 mW / cm², and the irradiation time is 50-70 s.
[0040] During the UV curing process of the present invention, 365nm UV light (light intensity 1000-1500mW / cm²) is irradiated for 50-70 seconds. The photoinitiator decomposes to produce free radicals (for example, 1-hydroxycyclohexyl phenyl ketone decomposes into cyclohexyl phenyl radicals and hydroxyl radicals), which trigger a free radical polymerization reaction of the double bonds (C=C) in the modified polyurethane acrylate and the base polyurethane acrylate, forming a three-dimensional network cross-linked structure. The cross-linking density is controlled by the light intensity, time, and resin system (the ratio of the terminal hydroxyl groups of the modified polyurethane acrylate to the double bonds of the base polyurethane acrylate). The final coating achieves high hardness, scratch resistance, and weather resistance through the cross-linked structure. At the same time, the hard skeleton of the modified nano-alumina and the elastic network of the resin synergistically enhance the wear resistance of the coating. The adhesion is significantly improved due to the strong binding force between the interfacial ester groups and the resin.
[0041] The beneficial effects of the present invention are: The present invention achieves a comprehensive improvement in coating performance through the collaborative innovation of materials and processes. First, nano-alumina is modified with stearic acid to form a stable ester layer on the surface of the nanoparticles through an esterification reaction, which significantly enhances its compatibility with the resin matrix, thereby increasing the hardness of the coating while maintaining flexibility, effectively resisting daily friction and minor impacts, and reducing scratches. Secondly, the modified polyurethane acrylate optimizes the cross-linking structure of the resin molecular chain through the gradual reaction of the terminal isocyanate prepolymer and the hydroxyl compound, which not only improves the chemical corrosion resistance of the coating, but also improves the adhesion to the substrate, avoiding coating peeling due to external force impact. In addition, the synergistic effect of the multi-agent system (such as photoinitiator, leveling agent and antioxidant) further improves the curing efficiency and surface uniformity of the coating, ensuring that the protective film maintains high transmittance and stability during long-term use.
[0042] The present invention solves the problems of traditional coatings' aging and poor weather resistance through precise control of process parameters. During the preparation process, the ultrasonic dispersion and reflux reaction conditions (such as temperature and time) of the nano-alumina are optimized to ensure uniform dispersion of the nanoparticles and sufficient surface modification, effectively suppressing agglomeration and improving the density and mechanical strength of the coating. At the same time, the specific wavelength and light intensity parameters of the UV curing process are designed to enable the resin system to quickly complete the cross-linking reaction, forming a three-dimensional network structure, significantly improving the coating's weather resistance and resistance to UV degradation. Furthermore, the temperature and time control of the pre-drying step effectively balance the solvent volatilization rate with the internal stress of the coating, avoiding the formation of microcracks caused by thermal stress and extending the service life of the coating.
[0043] This invention's breakthrough in comprehensive performance lies in the synergistic achievement of high hardness (pencil hardness ≥ 2H), strong adhesion (100-grid test peeling rate ≤ 5%), and long-term weather resistance (yellowing rate ≤ 10% after UV aging). By optimizing the interface between the nanoparticles and the resin, the coating combines wear resistance (rubbing times ≥ 5000 times) with impact resistance, adapting to the complex operating conditions of automotive surfaces. Furthermore, the use of environmentally friendly solvents and low-migration additives ensures that the coating meets green manufacturing standards and releases no harmful substances. This technology not only provides an innovative solution for automotive protection but can also be expanded to surface protection applications in areas such as electronic devices and architectural curtain walls, offering significant economic benefits and social value. DETAILED DESCRIPTION
[0044] The following specific implementation methods are only used to further illustrate the present application and should not be understood as limiting the scope of protection of the present application. Technicians in this field may make some non-essential improvements and adjustments to the present application based on the above application content.
[0045] 1. Implementation Example 1 A method for preparing an automotive surface protective material includes 10g of modified nano-alumina (50nm particle size), 30g of modified polyurethane acrylate, 35g of polyurethane acrylate, 5g of a photoinitiator (1-hydroxycyclohexyl phenyl ketone), 1g of a leveling agent (polyether-modified polydimethylsiloxane), 1g of an antioxidant (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), and 18g of ethyl acetate. The specific steps are as follows: Preparation of the modified nano-alumina: Add 50nm nano-α-Al2O3 to anhydrous ethanol and ultrasonically disperse for 60 minutes until uniformly dispersed (dispersion particle size ≤120nm). Add stearic acid to the dispersion, heat to 85°C, and reflux for 5 hours (with continuous stirring). After the reaction, filter while hot, wash the filter cake three times with anhydrous ethanol, and finally vacuum dry at 85°C for 24 hours. Preparation of modified polyurethane acrylate: Polycaprolactone diol and hexamethylene diisocyanate were added in appropriate proportions to a three-necked flask under nitrogen atmosphere. The temperature was raised to 80°C and allowed to react for 3.5 hours to produce an isocyanate-terminated prepolymer. Hydroxyethyl methacrylate and dibutyltin dilaurate were added, and the temperature was raised to 90°C for 2.5 hours to produce a hydroxyl-terminated polyurethane. Hydroxyethyl acrylate and 1-hydroxycyclohexyl phenyl ketone were then added and the reaction continued for 1.75 hours. Preparation of functional coating slurry: Modified nano-alumina was added to ethyl acetate and ultrasonically dispersed for 35 minutes. Modified polyurethane acrylate, polyurethane acrylate, photoinitiator, leveling agent, and antioxidant were added in sequence and stirred at 350 rpm for 25 minutes until uniformly mixed. Coating and curing: The slurry was applied to a 50μm-thick PET substrate using a doctor blade to a thickness of 30μm. Pre-dried at 85°C for 12 minutes, the slurry was then cured by irradiation with 365nm UV light (intensity 1200mW / cm²) for 60 seconds.
[0046] Example 2 Compared with Example 1, the difference is that the raw materials include 5g of modified nano-alumina (particle size 40nm), 20g of modified polyurethane acrylate, 40g of polyurethane acrylate, 3g of photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone), 0.5g of leveling agent (acrylate), 0.5g of antioxidant (tris(2,4-di-tert-butylphenyl) phosphite), and 21g of ethyl acetate. The process parameters are adjusted as follows: ultrasonic dispersion of nano-alumina for 50 minutes, reflux reaction for 4 hours, drying at 80°C for 20 hours; reaction temperature of modified polyurethane acrylate prepolymer for 3 hours at 75°C, and the time of subsequent steps is shortened to 2 hours (hydroxy polyurethane) and 1.5 hours (hydroxyethyl acrylate reaction); coating thickness is 20μm, pre-drying temperature is 80°C for 10 minutes, and UV irradiation is 50 seconds.
[0047] Example 3 Compared with Example 1, the raw materials included 15g of modified nano-alumina (particle size 100nm), 35g of modified polyurethane acrylate, 25g of polyurethane acrylate, 8g of photoinitiator (2,4,6-trimethylbenzoyl-diphenylphosphine oxide), 2g of leveling agent (BYK silicone), 1.5g of antioxidant (dilaudidiopropionate), and 13g of ethyl acetate. The process parameters were adjusted as follows: ultrasonic dispersion of the nano-alumina for 70 minutes, reflux reaction for 6 hours, drying at 100°C for 24 hours; reaction temperature of the modified polyurethane acrylate prepolymer for 4 hours at 85°C, with subsequent steps extended to 3 hours (hydroxy polyurethane) and 2 hours (hydroxyethyl acrylate reaction); coating thickness was 40μm, pre-drying temperature was 100°C for 15 minutes, and UV irradiation was performed for 70 seconds.
[0048] Comparative Example 1 Compared with Example 1, the difference is that the nano-alumina is not modified, and unmodified nano-α-Al2O3 (particle size 50 nm) is directly used, and the stearate esterification step is omitted.
[0049] Comparative Example 2 Compared with Example 1, the difference is that modified polyurethane acrylate is not used, ordinary polyurethane acrylate is used instead of the modified product, and the addition step of hydroxyethyl methacrylate and hydroxyethyl acrylate is omitted.
[0050] Comparative Example 3 Compared with Example 1, the difference is that the coating thickness is adjusted to 50 μm (outside the scope of the claim), the pre-drying temperature is reduced to 70° C., the time is shortened to 8 minutes, and the UV irradiation time is extended to 90 seconds.
[0051] 2. Performance Testing The protective films prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests according to the following methods: 1. Pencil hardness test: In accordance with GB / T 6739-86, use a Mitsubishi UNI-ball hardness tester (pen refill model UNI-50, hardness grade 6H-6B). The specimen is fixed on a horizontal test bench. The pencil is at a 45° angle to the specimen surface. Apply a pressure of 1 kg and scratch a distance of 1 cm at a speed of 1 mm / s. After each stroke, replace the pencil with a pencil of the same hardness and re-grind the pencil tip. Repeat 5 times to determine the maximum pencil hardness that penetrates the substrate without leaving a scratch (e.g., 2H requires ≤ 2 penetrations out of 5).
[0052] 2. 100-grid test: According to ISO 2409, use a 100-grid knife (1mm spacing between teeth) to draw a 10×10 grid on the surface of the sample (depth to the substrate). After cleaning with a soft brush, apply 3M 610 tape vertically and tear it off. Observe the percentage of the area that has fallen off. Grade 0B means no falling off, and grade 5B means falling off >65%.
[0053] UV aging test: Refer to GB / T 16422.3-2014, using Q-LAB QUV / spray equipment, UVA-340 lamps (340nm wavelength), irradiation intensity of 0.89W / m², temperature of 60°C, humidity of 50%, for 1000 hours, and recording the yellowing index ΔE (measured with a colorimeter) and surface cracking.
[0054] 3. Wear resistance test: According to ASTM D4060, a Taber CS-10 abrader was used. The CS-10 grinding wheel was loaded with 1 kg and rotated at 250 rpm. The wear volume (mm³) was measured after 1000 revolutions. The grinding surface was perpendicular to the sample surface, and a dust collector was used to remove dust in real time.
[0055] 4. Adhesion test: According to GB / T 9286-1998, after cross-cutting, peel off the 3M 610 tape. Level 0 means no peeling, and level 5 means peeling >65%. The cross-cut direction is perpendicular to the texture of the specimen. After applying the tape, let it stand for 30 seconds before peeling it off.
[0056] 5. Chemical resistance test: Soak the sample in 30% H2SO4 or 40% NaOH solution for 72 hours, observe the bubbling, color change and quality change, and the corrosion rate is ≤0.1mg / cm²·h to pass.
[0057] 6. Thermal stability test: According to GB / T 2951.42-2008, the temperature was raised to 600°C at 10°C / min using a thermogravimetric analyzer (TGA), and the 5% weight loss temperature (Td5%) was recorded. The sample mass was ≥ 10 mg and the atmosphere was nitrogen (50 mL / min).
[0058] 7. Contact angle test: DataPhysics OCA 20 sessile drop contact angle meter was used, deionized water drop (volume 5μL), contact angle measurement range 0-180°, three measurements were averaged, and surface energy was calculated using Young's equation.
[0059] 8. Tensile test: According to GB / T 528-2009, dumbbell-shaped specimens (2 mm thick) were stretched at a rate of 500 mm / min on a universal testing machine until they broke. The tensile strength (MPa) and elongation at break (%) were recorded. The distance between the clamps was 50 mm.
[0060] 9. Volume Resistivity Test: In accordance with GB / T 1410-2006, measure the surface resistance (Ω) of the sample using a Keithley 6517B megohmmeter with a 1000V DC voltage applied. The electrode spacing is 10mm and the ambient humidity is ≤50%. Key Parameter Controls: All tests are conducted at a temperature of 23±2°C and a humidity of 50±5%. Samples must be preconditioned under standard conditions for 24 hours. Before testing, the surface must be clean and free of oil. Data is recorded to two decimal places. The test is repeated three times and the average value is calculated.
[0061] 10. Performance test results: Table 1: Performance test results of various embodiments and comparative examples
[0062] As shown in Table 1, by comparing the performance test results of Examples 1-3 with those of Comparative Examples 1-3, the new automotive protective material of the present invention demonstrates significant improvements in hardness, wear resistance, adhesion, and weather resistance, systematically addressing the core pain points of traditional automotive protective materials. In terms of hardness, the pencil hardness of Examples 1-3 reaches 2H-3H, while that of Comparative Examples 1-3 is only 1H. This is due to the synergistic effect of the modified nano-alumina (stearate-treated) and the highly cross-linked polyurethane acrylate: the stearic acid modification forms a stable ester layer on the surface of the nano-alumina, enhancing the interfacial bonding with the resin matrix. Simultaneously, the polyurethane acrylate forms a dense cross-linked network through the gradual reaction of terminal hydroxyl groups with isocyanate groups. These two factors together enhance the coating's scratch resistance, effectively addressing the low hardness of traditional materials caused by uneven filler dispersion or insufficient resin cross-linking. In terms of wear resistance, the wear volume of Example 1-3 was only 0.8-1.5 mm³ (after 1000 revolutions), far lower than the 3.5-5.8 mm³ of Comparative 1-3. This is primarily due to the introduction of nano-alumina as a hard filler. Its high hardness (Mohs hardness 9) combined with the elastic network of the resin forms a "hard skeleton + flexible matrix" structure, which not only resists direct impact from external friction but also absorbs some energy through resin deformation, reducing local damage to the coating. In contrast, the poor dispersibility of the unmodified nano-alumina (prone to agglomeration) and the simple resin system (lack of an elastic network) in the Comparative 1-3 coatings lead to cracking and shedding due to friction, significantly accelerating the wear rate. Adhesion is also significantly improved: the shedding rate of the 100-grid test for Example 1-3 is 0% (level 0), while the shedding rate for Comparative 1-3 is 5%-30% (levels 2-4). This improvement stems from two factors: first, the ester layer on the surface of the modified nano-alumina forms a mechanical bond with the substrate (such as PET / TPU), enhancing interfacial adhesion; second, the addition of a leveling agent (such as polyether-modified polydimethylsiloxane) optimizes coating leveling, reduces surface defects (such as craters and orange peel), and prevents delamination due to stress concentration. In the comparison columns, due to the weak affinity of the unmodified nano-alumina with the substrate and the lack of an optimized leveling process, the coating is prone to detachment under stress due to weak interfacial bonding or surface defects. The breakthrough in weather resistance is reflected in the performance after UV aging: after 1000 hours of UV aging, the yellowing index ΔE of the implementation columns 1-3 was only 1.2-2.0, with no noticeable cracking; in contrast, the ΔE of the comparison columns 1-3 reached 4.8-6.3, with severe cracking. This is mainly due to the synergistic effect of antioxidants (such as pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) and photoinitiators (such as 1-hydroxycyclohexyl phenyl ketone) added to modified polyurethane acrylates - antioxidants capture free radicals to inhibit oxidative degradation, and photoinitiators promote deep cross-linking of resins to form a stable network; at the same time, the shielding effect of nano-alumina reduces ultraviolet penetration, further reducing the aging rate of the resin.The comparative example lacks a modified polyurethane acrylate (lacking an antioxidant and photoinitiator synergistic system) and unmodified nanoalumina (poor dispersibility and ineffective UV shielding), resulting in the resin being susceptible to photooxidative degradation, yellowing, and cracking. In summary, Examples 1-3 systematically address the low hardness, poor wear resistance, weak adhesion, and insufficient weather resistance of traditional protective materials through nanoalumina modification (stearate enhancement to enhance interfacial bonding), optimization of the polyurethane acrylate system (introduction of terminal hydroxyl groups to increase crosslinking density), additive synergy (antioxidant + photoinitiator to inhibit aging), and precise control of process parameters (ultrasonic dispersion, pre-drying, and UV curing conditions), significantly improving the overall performance of the coating.
[0063] The above-described embodiments merely illustrate several implementations of the present invention. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, and all such variations and improvements fall within the scope of protection of the present invention.
Claims
1. An automobile surface protective material, characterized in that: In terms of mass percentage, the raw materials include: Modified nano-alumina: 5-15%; Modified polyurethane acrylate: 20-35%; Polyurethane acrylate: 25-40%; Photoinitiator: 3-8%; Leveling agent: 0.5-2%; Antioxidant: 0.5-1.5%; Solvent: balance; The preparation steps of the modified nano-alumina include: adding nano-α-Al2O3 to anhydrous ethanol and ultrasonically dispersing until uniform dispersion; adding stearic acid to the dispersion, heating to 80-90°C and reflux reaction, continuously stirring during the reaction to promote the esterification reaction between hydroxyl groups and stearic acid; filtering while hot after the reaction is completed, washing the filter cake with anhydrous ethanol three times, and finally drying in a vacuum.
2. The automobile surface protective material according to claim 1, characterized in that: The preparation steps of the modified nano-alumina include: the particle size of the nano-α-Al2O3 is 40-100nm, the ultrasonic dispersion time is 50-70min; the particle size of the dispersion liquid is ≤120nm; the reflux reaction time is 4-6h; the vacuum drying temperature is 80-100℃ and the drying time is 20-24h.
3. The automobile surface protective material according to claim 1, characterized in that: The preparation steps of the modified polyurethane acrylate include: adding polycaprolactone diol and hexamethylene diisocyanate into a three-necked flask equipped with a stirrer and a thermometer, introducing nitrogen protection, heating to 75-85°C for reaction to obtain an isocyanate-terminated polyurethane prepolymer; adding hydroxyethyl methacrylate and dibutyltin dilaurate to the prepolymer, heating to 85-95°C for reaction to obtain a hydroxyl-terminated polyurethane; and then adding hydroxyethyl acrylate and 1-hydroxycyclohexyl phenyl ketone to the system for further reaction.
4. The automobile surface protective material according to claim 3, characterized in that: The reaction time when the temperature is raised to 75-85°C is 3-4 hours; the reaction time when the temperature is raised to 85-95°C is 2-3 hours; the reaction time is continued for 1.5-2 hours.
5. The automobile surface protective material according to claim 1, characterized in that: The photoinitiator is selected from at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide; the leveling agent is selected from at least one of BYK chemical silicone leveling agents, polyether modified polydimethylsiloxane and acrylate leveling agents.
6. The automobile surface protective material according to claim 1, characterized in that: The antioxidant is selected from at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris(2,4-di-tert-butylphenyl) phosphite and didodecyl thiodipropionate; and the solvent is ethyl acetate.
7. A method for preparing an automobile surface protective material according to any one of claims 1 to 6, characterized in that the steps include: S1. Add modified nano-alumina into solvent and disperse it uniformly by ultrasonication; Adding modified polyurethane acrylate, basic polyurethane acrylate, photoinitiator, leveling agent and antioxidant to the dispersion in sequence, stirring and mixing to obtain a functional coating slurry; S2. The functional coating slurry is evenly applied to the surface of the PET substrate by a doctor blade, and the coated substrate is placed in an oven for pre-drying; S3. Irradiate with a UV curing machine to complete the coating curing.
8. The preparation method according to claim 7, characterized in that In step S1, the ultrasonic dispersion time is 30-40 min; the stirring speed is 300-400 rpm, and the stirring time is 25-30 min.
9. The preparation method according to claim 7, characterized in that In step S2, the thickness of the PET substrate is 40-70 μm, the coating thickness is 20-40 μm, the pre-drying temperature is 80-100° C., and the pre-drying time is 10-15 minutes.
10. The preparation method according to claim 7, characterized in that In step S3, the wavelength of the ultraviolet light is 365 nm, the light intensity is 1000-1500 mW / cm², and the irradiation time is 50-70 s.
Citation Information
Cited By
Anti-fouling road marking composition based on hydrophobic nano-material and preparation method of anti-fouling road marking composition
CN121136588A
Polymer composite anti-aging bird-preventing umbrella cover and preparation method thereof
CN121406102A
